NATURAL ORGANIC MATTER AT OXIDE/WATER INTERFACES: COMPLEXATION AND CONFORMATION - MODELS AND MEASUREMENTS - Au K.K.; Penisson A.C.; Yang S.; O'Melia C.R. (My University, 1999)
A conceptual model for the adsorption of linear, flexible weak polyelectrolytes on oxide surfaces is applied to the adsorption and conformation of natural organic matter (NOM) on hematite. The polyelectrolytic nature of NOM and the complexation (specific) interactions between the functional groups of NOM and oxide surface sites are taken into account in this model. Model results are compared with experimental data for adsorption of Suwannee River humic acid on hematite at different pHs and ionic strengths. When the initial surface charge of hematite is positive (termed the oppositely charged case), the experimental adsorption density and adsorbed hydrodynamic layer thickness decrease with increasing pH and with decreasing ionic strength. When the initial surface charge is negative (termed the similarly charged case), the experimental adsorption density decreases with increasing pH and the adsorbed hydrodynamic layer thickness increases with increasing pH. Model results with a reaction represented by >MeOH + L- = >MeOHL- agree with the experimental adsorption density and adsorbed hydrodynamic layer thickness for the oppositely charged case, and the adsorption density for the similarly charged case. This suggests that the adsorption of NOM on hematite is related to the polyelectrolytic nature of NOM and to the complexation interactions between the neutral surface sites of oxides and the deprotonated functional groups of NOM. The effects of solution chemistry on the adsorption of NOM are due to a great extent to its effects on surface and NOM speciation, which can influence the specific interactions between NOM and surface sites. Model calculations also indicate that for the oppositely charged case, the adsorbed NOM overcompensates for the positive charge of the hematite surface. Simulations of electric potential and volume fraction indicate an interrelationship between the adsorption of NOM and interfacial properties.